Maternal-fetal attachment during pregnancy at the Public Health Center - Suryaningsih, Endang Koni; Aryudaningrum, Nastiti; Linh, Nguyen Dieu (International Journal of Health Science and Technology, 2024)
Maternal-fetal attachment (MFA) makes an essential contribution to maternal and fetal health and influences the adoption of a healthy lifestyle during pregnancy. Mothers who have a strong MFA tend to have healthy behaviors and give birth to healthy babies. Mothers who feel emotionally connected to their fetus tend to be more motivated to take care of their own health. They realize that their health directly affects the health of the developing baby. The purpose of this study is to provide an overview of maternal-fetal attachment in primigravida in the third trimester. The quantitative descriptive research method was used with 85 primigravida mothers who have met the inclusion criteria (third-trimester primigravida; no complications during pregnancy, self-examination at the Sleman regional public health centre) and have participated in this study. The Indonesian version of the Prenatal Attachment Inventory (PAI) questionnaire is used to review maternal-fetal attachments in a face-to-face interview. The results of the study provide an overview of the fact that most primigravida mothers in the third trimester have high maternal-fetal attachment scores. In addition, effective information communication and education for pregnant women were identified as factors that contributed to the level of maternal-fetal attachment. Effective maternal-fetal attachment-related programs in the education of new-reproductive couples are needed to be developed and implemented by health workers, including by midwives.